Gelatinases A and B activities in the serum of patients with various coronary artery disease stages - Radenković Sandra; Brajović Milan; Konjević Gordana; Gopčević Kristina (Vojnosanitetski Pregled)
Background/Aim. The main characteristic of matrix metalloproteinases (MMPs) is the degradation of extracellular matrix. Synthesis of MMPs has been reported in coronary atherosclerotic lesions in patients with coronary disease (CD) suggesting a pathogenic role of MMPs in its development. Recently there is increasing evidence that gelatinase A (pro MMP-2) and gelatinase B (proMMP-9) play a pathogenic role in the development of the atherosclerotic plaques. The aim of the study was to determine, by the use of a gel image system, a possible presence of active gelatinases in the serum of the patients with CD, as well as if their activity is higher in these patients than in healthy people. Methods. By gelatin zymography we analyzed the activity of proMMP-2 and proMMP-9 in the serum of 50 patients with various coronary artery disease stages and in the serum of 15 healthy controls. The activity was measured by using a gel image system (Kodak Image 1D 3.6.). Results. ProMMP-2 and proMMP-9 activity was significantly higher in the serum of patients with CD compared to controls. There was higher activity of MMP-2 and MMP-9 in the serum of patients with acute myocardial infarction (AMI) compared to patients with stable angina pectoris, as well as higher proMMP-9 activity in patients with unstable angina pectoris compared to patients with stable angina pectoris. Conclusion. ProMMP-2 and proMMP-9 participate in processes associated with destabilizing plaques and understanding the processes of MMPs activation and regulation may have significant benefits in clinical interpretation. The reported higher proMMP-2 and proMMP-9 activity in the serum of patients with CD suggests a role of proMMP-2 and proMMP-9 in prognostic stratification of these patients and in designing new drugs.